2021
DOI: 10.3390/md19030161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinal Lipid Absorption by Cyanobacterial Strains in Zebrafish Larvae

Abstract: Obesity is a complex metabolic disease, which is increasing worldwide. The reduction of dietary lipid intake is considered an interesting pathway to reduce fat absorption and to affect the chronic energy imbalance. In this study, zebrafish larvae were used to analyze effects of cyanobacteria on intestinal lipid absorption in vivo. In total, 263 fractions of a cyanobacterial library were screened for PED6 activity, a fluorescent reporter of intestinal lipases, and 11 fractions reduced PED6 activity > 30%. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Wild Mexican B. monnieri extracts are rich in carotenoids, which may have contributed to the observed anti-obesity and anti-inflammatory activity. Our results agree with previous studies, in which the promising effects of extracts or fractions from different sources were observed, such as the effect of cyanobacteria on the intestinal lipid uptake of zebrafish [ 44 , 45 ] and the reduction of neutral lipids by seagrass [ 46 ] or by actinobacteria [ 47 ], but of which the responsible metabolites are still to be identified, as is the case with B. monnieri .…”
Section: Discussionsupporting
confidence: 92%
“…Wild Mexican B. monnieri extracts are rich in carotenoids, which may have contributed to the observed anti-obesity and anti-inflammatory activity. Our results agree with previous studies, in which the promising effects of extracts or fractions from different sources were observed, such as the effect of cyanobacteria on the intestinal lipid uptake of zebrafish [ 44 , 45 ] and the reduction of neutral lipids by seagrass [ 46 ] or by actinobacteria [ 47 ], but of which the responsible metabolites are still to be identified, as is the case with B. monnieri .…”
Section: Discussionsupporting
confidence: 92%
“…The other 12 peaks with no match in the searched databases may represent novel compounds. In accordance, many studies using similar untargeted metabolite profiling approaches demonstrated a large percentage of not-known compounds, which still remain to be isolated and identified [24,[34][35][36]. In the future, CH-UAE extract should be fractionated to reduce the complexity of the material and identify the responsible compounds for the observed anti-obesity activity.…”
Section: Discussionmentioning
confidence: 95%
“…As described by Bellver et al [34], molecular networking analysis was conducted with some modifications. Raw data were converted using the software program MSConvert to mzXML format for molecular networking and metabolomic analysis.…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…Microalgae and cyanobacteria are well-known sources of compounds with many bioactivities. 8,10,[28][29][30][31] However, research in this field is still underexplored and for the first time, the potential of lactic acid fermentation of microalgae was studied as a tool to enhance the production of bioactive compounds with lipid reducing activity. Recent studies demonstrated some lipid reducing activity of fermented cauliflower fungus (Sparassis crispa) on diet induced obese zebrafish with promis-…”
Section: Discussionmentioning
confidence: 99%
“…edu/) with the recommended standard parameter. The data analysis for the feature-based molecular networking are described in Bellver et al, 2021 28. 2.6 Statistical analysisGraphpad Prism (Version 8, San Diego, CA, USA) was used to create graphs and to develop statistical analyses.…”
mentioning
confidence: 99%